2000
DOI: 10.1038/sj.jhh.1000940
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic myocardial textural parameters and midwall left ventricular mechanics in essential arterial hypertension

Abstract: Background: The evaluation of the systolic left ventricular performance in hypertensive patients presents some problems related to left ventricular hypertrophy (LVH) which alters the ventricular geometry. The videodensitometric textural ultrasonic analysis of hypertensive myocardium has provided evidence of impairment in the cyclic variation of the mean gray level. This might be considered as an index of intrinsic myocardial function. Objectives: The aim of the present study was to analyse the connection betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…That CVI was unrelated to wall thickness per se was important, concordant with that demonstrated in athletes with left ventricular hypertrophy from isometric exercise. Interestingly, Di Bello et al 3 found correlations in hypertensive patients between CVI in the septum and left ventricular posterior wall and midwall fractional shortening, and novel inverse correlations between CVI, systolic blood pressure, left ventricular mass and end-systolic wall stress. The correlations between CVI, blood pressure and myocardial mass were weak, but their directions were consistent with the logic that the higher the arterial blood pressure the greater the left ventricular mass, the more chronic and severe the hypertension, the greater likelihood of interstitial fibrosis and the more intense the backscatter.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 98%
“…That CVI was unrelated to wall thickness per se was important, concordant with that demonstrated in athletes with left ventricular hypertrophy from isometric exercise. Interestingly, Di Bello et al 3 found correlations in hypertensive patients between CVI in the septum and left ventricular posterior wall and midwall fractional shortening, and novel inverse correlations between CVI, systolic blood pressure, left ventricular mass and end-systolic wall stress. The correlations between CVI, blood pressure and myocardial mass were weak, but their directions were consistent with the logic that the higher the arterial blood pressure the greater the left ventricular mass, the more chronic and severe the hypertension, the greater likelihood of interstitial fibrosis and the more intense the backscatter.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 98%